TINGKAT KESALAHAN PERUBAHAN VERBA KAUSATIF DALAM KALIMAT BAHASA JEPANG MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Putri Zarista; Mangatur Sinaga; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to explain the level of errors made by students in changing causative verbs in Japanese sentences. This research is a type of quantitative descriptive research. The instrument used in this research is a test instrument. The data processing method uses statistical formulas. The results of this study show that the error rate of causative verb changes in Japanese sentences is high, with a percentage of 76%.Key Words: causative verb, error rate.